KERJA PEGAWAI DI KANTOR PUSAT PELATIHAN DAN PENGEMBANGAN KAJIAN MANAJEMEN PEMERINTAH LEMBAGA ADMINISTRASI NEGARA KOTA MAKASSAR - Nurasisah, Nurasisah; Burhanuddin, Burhanuddin; Parawu, Hafiz Elfiansyah (Universitas Muhammadiyah Makassar, 2022)
ABSTRACTThe purpose of this study was to find out the effect of performance assessment on employee performance at the Central Office of Training and Development of Government Management Studies at the Makassar City State Administration. This study used a quantitative research type with causal associative quantitative research type from 68 populations to be studied. The results of this study showed that the regression results (influence) of Variable X on Variable Y simultaneously were only 0.312 or 31.2%, which meant that the effect of Performance Assessment on Employee Work Performance in the office was relatively small. While the effect of the Performance Assessment variable (X) on Work Performance (Y) partially showed the results each indicators had bad effect of no more than 0.162 or 16.2%, it also showed the effect of Performance Assessment on Employee Work Performance at the Center for Management Studies Training and Development. The government of the Makassar City State Administration Agency is relatively small.Keywords : Performance Assessment, Work Achievement